Hepatocellular carcinoma: an evolving challenge in viral hepatitis and HIV coinfection. (13th March 2017) - Pinato, David J.; Dalla Pria, Alessia; Sharma, Rohini; Bower, Mark
Abstract : Liver-related morbidity and mortality is expanding in people living with HIV. Hepatocellular carcinoma (HCC), the third most lethal malignancy on a global scale, is a dominant complication of chronic liver disease and cirrhosis in patients with coexisting hepatitis. HIV infection further complicates the clinical heterogeneity of HCC, posing concurrent challenges stemming from the underlying immunological status of the patients and the ongoing need for combined antiretroviral therapy. In this article, we review the multiple clinical implications that characterize the multidisciplinary management of HCC in the context of HIV infection.